Upfront surgery is not advantageous compared to more conservative treatments such as observation or medical treatment for patients with desmoid tumors - Tsukamoto, Shinji (BMC Musculoskelet Disord, 2021)
BACKGROUND: This study compared the clinical and functional outcomes of patients initially treated with observation or medical treatment with those of patients treated with local treatment (surgery alone or surgery with adjuvant radiotherapy) to confirm whether observation or medical treatment is an appropriate first-line management approach for patients with desmoid tumors. METHODS: We retrospectively reviewed the medical records of 99 patients with histologically confirmed primary desmoid tumors treated between 1978 and 2018. The median follow-up period was 57 months. We evaluated event-free survival, defined as the time interval from the date of initial diagnosis to the date of specific change in treatment strategy or recurrence or the last follow-up. RESULTS: An event (specific change in treatment strategy or recurrence) occurred in 28 patients (28.3%). No significant difference in event-free survival was found between the first-line observation/medical treatment and local treatment groups (p = 0.509). The median Musculoskeletal Tumor Society score of the patients treated with first-line local treatment was 29 (interquartile range [IQR], 23–30), whereas that of the patients managed with first-line observation or medical treatment was 21 (IQR, 19–29.5). First-line observation or medical treatment was more frequently chosen for larger tumors (p = 0.045). In the patients treated with local treatment, local recurrence was not related to the surgical margin (p = 0.976). CONCLUSION: Upfront surgery is not advantageous compared to more conservative treatments such as observation or medical treatment for patients with desmoid tumors. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12891-020-03897-9.